IMAGE OF THE TYUMEN REGION IN OBJECTIVE AND SUBJECTIVE MEASUREMENTS: A COMPARATIVE ANALYSIS - Olga S. Pustoshinskaia (Сравнительная политика, 2018)
The article is devoted to the problems of regional positioning as the most important factor in the growth of the symbolic potential of the state, whose political and social communities are interested in the sustainable and progressive development of their territories. The authors, based on the results of the conducted research, assess the progress in the semantic fi elds of the attractive image of the Tyumen region. Image models are considered for the purpose of revealing the similarities and differences in the characteristics expressed in them. It is established that the objective image integrates positive and problem manifestations of regional reality. In subjective constructions, negative aspects do not fi nd fi xation. The dynamics in the perception of the Tyumen region by the population of Russia is revealed. In the matrix of mental design there are many new associates replacing part of the core brand of hydrocarbon specialization and referring to the diversifi cation of the economy, its innovative restructuring, historical and cultural heritage, sports and scientifi c achievements, and tourism opportunities. In the representations of citizens of the CIS countries, the uniqueness of the Tyumen region is associated with the exportraw material supply, as well as a capacious labor market, favorable conditions for training, life, self-realization. The European countries do not have the necessary level of recognition of the region. The oil and gas component in Western societies is more closely associated with the image of the Russian Federation as a whole as an energy power. The set of image features is reduced to the limits of immersion in business, educational, sports and other communications within the framework of international cooperation.